Hydrated negative air ions generated by air–water collision with TiO2 photocatalytic materials. Issue 71 (8th December 2020) - Zhang, Chaoying; Wu, Zengnan; Wang, Chang; Li, Haifang; Li, Zenghe; Lin, Jin-Ming
Abstract : Illustration of a hydrated negative air ion generation system, water droplets and O2 molecular capture electrons generated by TiO2 to form water cluster ions. Abstract : Photocatalytic materials are often used in the field of electrolysis of water for its competitive performance and low cost. This study describes the use of TiO2 for providing free electrons to prepare hydrated negative air ions together with the Lenard effect caused by air–water collision. The lifetime of HNAIs increased by 47.62% in comparison with the traditional corona discharge method; both the stability and the actual yield of the HNAIs increased significantly. The stability of HNAIs has a correlative relationship with the molecular weight and relative humidity. Lower mobility of the HNAIs with larger molecular weight results in low probability of collision with other air particles, making it relatively stable. Water molecules could form a water shell around the cluster ions in a high relative humidity environment, which can protect the ions, avoiding physical collision to extend the lifetime.